Gastrointestinal Complications Following Abdominal Sacrocolpopexy for Advanced Pelvic Organ Prolapse - Whitehead, William E. (2007)
OBJECTIVES: The aims of this secondary analysis of the “Colpopexy And Urinary Reduction Efforts” (CARE) study were to estimate the incidence of post-operative gastrointestinal complications and identify risk factors. STUDY DESIGN: We prospectively identified gastrointestinal complications and serious adverse events (SAE) for 12 months after sacrocolpopexy. Two surgeons independently reviewed reports of ileus or small bowel obstruction (SBO). RESULTS: Eighteen percent of 322 women (average age 61.3 years) reported “nausea, emesis, bloating, or ileus” during hospitalization and 9.8% at 6 weeks. Nineteen women (5.9%; CI 3.8%, 9.1%) had a possible ileus or SBO that generated SAE reports: four (1.2%, CI 0.5%,3.2%) were re-operated for SBO, 11 (3.4%, CI 1.9%,6.1%) were readmitted for medical management, and four had a prolonged initial hospitalization. Older age (p<0.001) was a risk factor for ileus or SBO. CONCLUSIONS: One in twenty women experiences significant gastrointestinal morbidity after sacrocolpopexy. This information will aid pre-operative counseling.